Physicochemical characterisation of fluorohectorite: Water dynamics and nanocarrier properties - Larsen, Simon R.; Michels, Leander; dos Santos, Éverton C. [UNESP]; Berg, Marcella C.; Gates, Will P.; Aldridge, Laurie P.; Seydel, Tilo; Ollivier, Jacques; Telling, Mark T.F.; Fossum, Jon Otto; Bordallo, Heloisa N. (Elsevier, 2020)
Clay minerals such as fluorohectorite (FHt) have come into prominence as drug carrier systems due to their layered structure and excellent cation exchange capabilities. Water present in the interlayers of FHt is believed to facilitate the uptake of bio-active molecules in these systems, yet details of this interaction are not well understood. To shed light into this question, using quasi-elastic neutron scattering and the jump diffusion model, we determined the diffusion coefficients and the residence time of water in this synthetic smectite clay. We demonstrate how different interlayer cations (Li+, Na+ and Ni2+) and different hydration levels influenced water mobility in FHt. By means of the elastic window method and analysis of the thermal decomposition of samples with the drug Ciprofloxacin intercalated at pH 2 in LiFHt, we confirmed that the intercalation process removed most of the interlayer water previously present in the clay. Based on the Kissinger procedure, we also showed that thermal decomposition of the intercalated drug was activated at lower temperature. These findings are discussed in relation to the drug's shelf life and might aid in the selection of clay systems for use as nanocarrier.
Keywords: Clay mineral; Decomposition kinetics; Nanocarrier; Neutron spectroscopy; Water mobility